Ability of arbuscular mycorrhizal to protect tomato (Solanum lycopersicum) seedlings from Fusarium oxysporum - ZEHAIRA, BOUZIANE; LAID, DEHIMAT (The Indian Journal of Agricultural Sciences, 2023)
Present experiments were conducted in the microbiology laboratory, Department of Environmental and Agronomic Sciences and in a private nursery in the Tassoust region of Jijel during 2021 and 2022. This study was carried out on the use of strains of arbuscular mycorhizal fungi (Acaulospora sp. and Glomus sp.) as a means to control F. oxysporum effect. After 15 days of inoculation, several measurements of the lengths roots, stem and leaves were noted and symptoms of Fusarium disease were also recorded. The results revealed that F. oxysporum is a pathogen for tomato (Solanum lycopersicum L.) plants (super strain) variety, causing Fusarium disease of this host, which manifests by yellowing, wilting and necrosis of aerial parts, and reduced growth parameters in plants. Therefore, the disease incidence after 15 days of inoculation is estimated at 75 and 50% for (T1 and T3) respectively. In addition, our results revealed that the percentage of incidence was 100 and 25% respectively for T1 and T3 after 22 days. Whereas, the results showed that mycorhizal fungi are associated with the roots of tomato plants. They reduced the incidence rate of Fusarium disease by 50% (T3) and improved the growth of tomato seedlings (Super strain) which manifests itself by a vigorous root system and a very important development of the aerial parts. These results indicate that arbuscular mycorhizal fungi can effectively contribute to the ecological management of soil-borne fungal disease.